Alexithymia and binge eating: Maladaptive emotion regulation strategy or deficient interoception?. (1st August 2022) - Lyvers, Michael; Kelahroodi, Mazaheri; Udodzik, Emily; Stapleton, Peta; Thorberg, Fred Arne
Abstract: Alexithymia has been linked to various excessive behaviors as a likely risk factor, including binge eating. Such relationships are often attributed to deficient emotional self-regulation in alexithymia, ostensibly leading to the use of maladaptive, externalized behaviors as strategies for coping with distress. An alternative view is that alexithymia reflects a fundamental deficit of interoceptive awareness that, in the case of binge eating, would suggest that internal satiety cues are poorly recognized, promoting overconsumption. The present study assessed the relationship between alexithymia and binge eating in the context of these competing hypotheses. A large online sample of young adults ( n = 532) completed validated measures of alexithymia, emotion regulation, interoception, binge eating, emotional eating motivation, and sensitivity to reward and punishment. Correlations were as expected except for interoception, which showed minimal association with alexithymia or binge eating. In a hierarchical regression controlling for age, gender, education level and student status as covariates, binge eating was predicted by emotional eating motivation, emotion regulation (a negative predictor), alexithymia, and reward sensitivity, with the final model explaining 53% of variance in binge eating. Bootstrapped path analyses controlling for all other variables indicated that the relationship between alexithymia and binge eating was mediated by deficient emotion regulation but not deficient interoception, and that the relationships of both alexithymia and emotion regulation with binge eating were mediated by emotional eating motivation. Results are consistent with the notion that the association of alexithymia with binge eating reflects deficient emotion regulation in alexithymia, which can lead to adoption of maladaptive, externalized behaviors such as binge eating for coping with distress.